Cu-Catalyzed Asymmetric Conjugate Addition of Dialkylzincs to Enones Using a (±)-trans-1,2-Cyclohexanediamine-Based Bis(NHC) Derived from l-Leucinol - Kamihigashi, Shun; Shibata, Naoatsu; Sakaguchi, Satoshi (Synlett, 2014)
A hydroxyamide-functionalized azolium salt as the precursor of a (±)-trans-1,2-cyclohexanediamine-based bis(NHC) ligand was designed and synthesized from readily accessible l-leucinol. The combination of a Cu salt with this chiral ligand precursor promoted the asymmetric conjugate addition of Et2Zn to 2-cyclohexen-1-one at room temperature without the need for temperature control to afford the corresponding 1,4-adduct with up to 95% ee.
Keywords: asymmetric catalysis; carbene complexes; copper; Michael addition; ligands